PERSEPSI HARGA BERPENGARUH TERHADAP MINAT MEMBELI DI THE 18th RESTAURANT AND LOUNGE THE TRANS LUXURY HOTEL BANDUNG - I Gusti Ayu Agung; Agnes Putri Aprilia (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2021)
Today, the world of tourism, especially in the hotel industry, is required to be able to serve various consumers and to be able to provide the best possible products. One of the means to carry out the food service industry is a restaurant. The number of hotel competitors currently triggers a hotel to continue to develop in order to create good quality for the community. Not only is the product the main factor in attracting customer buying interest, but the price perception aspect is also an important factor in buying interest at The 18th Restaurant and Lounge. The purpose of this study was to determine the perception of price as well as its effect on buying interest at The 18th Restaurant and Lounge. This study uses a qualitative method, with the technique of taking the research subject or informant used is purposive sampling. Informants in this study amounted to 5 (five) people. More specifically, the three informants selected in this study were guests who had or had the experience of visiting The 18th Restaurant and Lounge The Trans Luxury Hotel Bandung and Restaurant Manager. The data collection techniques used are interviews, observation and documentation and the data analysis technique used is descriptive qualitative with a constant comparative method. Checking the validity of the data used is data triangulation. The results of this study found how the customer price perception of The 18th Restaurant and Lounge, namely customers get price affordability, get a price match with the quality of the product received, and price compatibility with the benefits received causes the tendency of customers to repurchase or recommend to others. So it can be concluded that price perceptions about a product affect the emergence of customer buying interest.